A circular polarization-selective ultrafast all-optical switch based on a zero-refractive-index metasurface

By plating Au film on SiO2 substrate and depositing ITO film, a periodically arranged metal Au micro-nano structure layer was prepared, and the third-order nonlinear effect of ITO and the circular dichroism characteristics of chiral metasurface were solved in the prior art. The problem of insufficient selectivity for circular polarized light regulation has been achieved, and all-optical switches with high selectivity and femtosecond response are realized.

CN114153101BActive Publication Date: 2025-02-21BEIJING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111046827.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-07
Publication Date
2025-02-21
Estimated Expiration
2041-09-07

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high selective regulation of circularly polarized light, and the signal attenuation during transmission is large, which affects the accuracy of information transmission.

Method used

By plating an Au film on a SiO2 substrate and depositing an ITO film on the Au film, a periodically arranged metal Au micro-nano structure layer is prepared, and the third-order nonlinear effect of ITO and the circular dichroism characteristics of chiral metasurface are achieved. Selective reflection and regulation of circularly polarized light.

Benefits of technology

High selective regulation of circular polarized light is achieved, circular dichroism and third-order nonlinear effects are enhanced, and rapid regulation of femtosecond order and all-optical switches of micron size are realized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114153101B_ABST
    Figure CN114153101B_ABST
Patent Text Reader

Abstract

A circular polarization selective ultrafast all-optical switch based on a zero-refractive index material metasurface belongs to the technical field of all-optical switches. A 100-200nm thick Au film is deposited on a SiO2 substrate by vacuum thermal evaporation, a 100-120nm thick ITO film is deposited on the Au film by magnetron sputtering coating technology, and a periodically arranged metal Au micro-nano structure layer is prepared on the ITO film. It has strong selectivity for left-handed and right-handed polarized light. Using femtosecond laser control, the modulation speed is achieved at the femtosecond level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-optical switches, and in particular relates to a circular polarization selective ultrafast all-optical switch based on a zero-refractive-index material metasurface. Background Art

[0002] With the rapid development of the information society, information processing has put forward higher requirements for big data, low energy consumption, high-speed processing, etc. Photons have obvious speed advantages as information carriers, and light waves have different wavelengths, frequencies, polarization states and phase information, which can be used to represent different data information, thereby greatly increasing data capacity and improving data transmission speed, reducing system costs and working energy consumption.

[0003] An all-optical switch uses one beam of light to control the transmission state of another beam of light. Compared with optical switches using electro-optical, thermal-optical and other excitation methods, it has a faster control speed and is a very important integrated photonic device. Polarized light used for optical information transmission usually uses linearly polarized light or circularly polarized light. Circularly polarized light has very good polarization-maintaining properties and a small signal attenuation during transmission. There is little interference between circularly polarized lights, and the light transmission and light blocking properties are not affected by the rotation angle. Circularly polarized light includes left-handed circularly polarized (LCP) light and right-handed circularly polarized (RCP) light. In order to control the transmission state of the optical switch, the different polarization states of LCP light and RCP light can be fully utilized to select the reflection or transmission of the two polarization states.

[0004] The change in reflectivity of chiral materials under the excitation of LCP light and RCP light is called circular dichroism (CD). Most circularly polarized light switches utilize this property. There are also many chiral materials in nature, but their CD is relatively weak, and the selective reflection of circularly polarized light is not strong, so they are not suitable for direct use as devices. To enhance CD, chiral metasurfaces can be used. Chiral metasurfaces are mostly metal micro-nano structures. The CD of metal micro-nano structures is generated by the different distribution of electromagnetic fields excited by left-handed and right-handed circularly polarized light. Changes in structural geometric parameters affect the interaction between electric and magnetic dipole modes. Therefore, the strength of CD signals and characteristic wavelengths can be adjusted over a wide range by adjusting the structural parameters. In order to make full use of the changes in CD, this can be achieved through artificially prepared chiral metasurfaces. At the same time, sub-wavelength metasurface structures have demonstrated unprecedented flexibility in controlling light waves.

[0005] Third-order nonlinear optical materials are used to realize optical switching by light control, that is, under the stimulation of pump light, the optical Kerr effect causes the refractive index of the material to change. Near-zero dielectric constant (ENZ) materials, such as transparent conductive oxide indium tin oxide (ITO), have the advantages of high carrier concentration, sensitive refractive index change, and obvious nonlinear effect. However, the third-order nonlinear coefficient of the material is usually small, which makes it difficult to meet the needs of ultrafast optical control. Combining zero-refractive index materials with chiral metasurfaces can effectively enhance the third-order nonlinear effect and be used to realize circular polarization-dependent optical control.

[0006] Realizing circular polarization-selective ultrafast all-optical switching can not only promote the progress of quantum information technology and optical interconnection, but also promote the development of spin electronics, biosensors, analytical chemistry and other fields. Summary of the invention

[0007] When linearly polarized light is used as optical information transmission, its polarization direction is easily affected by external factors and changes. However, if circularly polarized light is used, the polarization state of the light can be guaranteed not to change, and thus the information carried will not change, thus ensuring the accuracy of information transmission. The metasurface of metal micro-nanostructures can achieve selective reflection of circularly polarized light and enhance CD. The nonlinear effect of ENZ materials can realize the regulation of optical switches. Currently, the widely used methods for dynamic CD regulation of chiral micro-nanostructures include mechanical regulation, thermal regulation, electrical regulation, optical regulation, etc. The nonlinear material selected in the present invention is ITO, because the third-order nonlinear effect of ITO is sensitive to pump light, and optical switches can be regulated by light, and the device can also achieve short-time response. The design of a micron-sized all-optical switch realizes the selection of the polarization state of circularly polarized light, and the switch response time is in the order of femtoseconds.

[0008] A circular polarization selective ultrafast all-optical switch based on a zero-refractive index material metasurface, characterized in that a layer of Au film with a thickness of 100-200 nm is deposited on a SiO2 substrate by a vacuum thermal evaporation process, an ITO film with a thickness of 100-120 nm is deposited on the Au film by a magnetron sputtering coating technology, and a periodically arranged metal Au micro-nano structure layer is prepared on the ITO film;

[0009] Each metal micro-nanostructure in the periodically arranged metal micro-nanostructure layer: from the top view of the metal micro-nanostructure layer, it includes three different rectangular structures: the first rectangular structure ① is 504nm long and 55nm wide; the second rectangular structure ② is 261nm long and 100nm wide; the third rectangular structure ③ is 218nm long and 60nm wide; the first rectangular structure ① strings the second rectangular structure ② and the third rectangular structure ③ together, and the second rectangular structure ② and the third rectangular structure ③ are strung together along the length direction of the first rectangular structure ①, that is, they intersect with the first rectangular structure ① at the same time, the second rectangular structure ② is located in the upper part of the length direction of the first rectangular structure ①, and the length direction of the second rectangular structure ② is rotated clockwise relative to the length direction of the first rectangular structure ① to form an angle θ1, and θ1 is 50°; the third rectangular structure ③ is located in the lower part of the length direction of the first rectangular structure ①, and the length direction of the third rectangular structure ③ is rotated clockwise relative to the length direction of the first rectangular structure ① to form an angle θ2, and θ2 is 60°.

[0010] The relative positions of the centers of the three rectangles are represented by coordinates. The coordinates of the center of the first rectangular structure ① are (0nm, 0nm), the center coordinates of the second rectangular structure ② are (-50nm, 22nm), and the third rectangular structure ③ is (-27nm, -172nm).

[0011] The thickness of the metal micro-nano structure layer, that is, the thickness of the three rectangles, is 50 nm.

[0012] The periodic arrangement is arranged in sequence at least along the width direction of the first rectangular structure ①.

[0013] The optical switch unit structure is as follows Figure 2 As shown, preferably from bottom to top are SiO2 substrate, 100nm thick Au, 100nm thick ITO, and 50nm thick gold micro-nano structure.

[0014] A method for preparing a circular polarization selective ultrafast all-optical switch based on a zero-refractive index material metasurface, characterized in that:

[0015] 1) Au film is deposited on SiO2 substrate by vacuum thermal evaporation process;

[0016] 2) Using magnetron sputtering coating technology, continue to deposit ITO film on the Au film;

[0017] 3) Using electron beam exposure technology to process a mask in the shape of a metal micro-nano structure on the ITO film;

[0018] 4) Au is evaporated using a vacuum thermal evaporation process to prepare a periodically arranged metal micro-nano structure on the ITO film.

[0019] Advantages and positive effects of the present invention:

[0020] 1) Circularly polarized light has polarization-maintaining properties and the signal attenuation during transmission is small. There is little interference between circularly polarized lights, and the light transmission and light blocking properties are not affected by the rotation angle.

[0021] 2) The designed chiral metasurface structure has strong selectivity for left- and right-polarized light.

[0022] 3) The third-order nonlinear effect of ITO is utilized to achieve rapid change of refractive index.

[0023] 4) Using femtosecond laser control to achieve modulation speed in the femtosecond range.

[0024] 5) The designed structure size is in micrometer size.

[0025] The positive effects of the present invention are to enhance circular dichroism and the third-order nonlinearity of ITO, have high selectivity for the polarization state of circularly polarized light, realize micron-sized all-optical switching, and realize rapid regulation at the femtosecond level. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the unit microstructure

[0027] Figure 2 Ultrafast optical switch unit structure design diagram

[0028] Figure 3 Reflectivity of RCP light and LCP light before and after pumping

[0029] Figure 4 On / Off Ratio Spectrum

[0030] Figure 5 Changes in CD value before and after pumping. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0032] Example 1

[0033] according to Figure 1 and Figure 2 The micron-sized chiral metasurface device is prepared by the structure to achieve ultrafast modulation of circularly polarized light.

[0034] 1) A 100 nm thick Au film is deposited on a silicon dioxide substrate using a vacuum thermal evaporation process. During evaporation, the current is adjusted to maintain the evaporation speed at Prevent uneven film thickness and ensure the hardness of the Au film.

[0035] 2) Using magnetron sputtering coating technology, continue to deposit 100nm thick ITO on the 100nm Au film. The deposition process uses magnetron sputtering, the RF source power is 70W, and the ITO target material is mixed with 90% In2O3 and 10% SnO2. The deposition is carried out at room temperature and the cavity pressure is 5m Torr. In order to provide cavity pressure during the sputtering process and achieve complete oxidation, a mixed gas consisting of argon and oxygen with a volume ratio of 10:1 is selected. After that, a vacuum annealing process can improve the surface quality and carrier concentration, and the annealing temperature is 350℃.

[0036] 3) Use electron beam exposure technology to process the gold structure mask. First, a layer of photoresist is spin-coated, and then the micro-nano structure is etched using electron beam exposure, and the structural pattern is obtained after development and fixing.

[0037] 4) Using a vacuum thermal evaporation process to evaporate 50 nm thick Au, a periodically arranged metal micro-nano structure was prepared, and the photoresist was peeled off to obtain a sample.

[0038] FIB etching can be used to prepare metal micro-nano structures on the ITO layer.

[0039] The structure was simulated using finite element analysis software (COMSOL). The gold structure on the ITO film is as follows: Figure 1 As shown, it consists of three different rectangles: the vertical rectangle ① at the center is 504nm long and 55nm wide; the horizontal rectangle ② at the top is 261nm long and 100nm wide, rotated 50° clockwise; the horizontal rectangle ③ at the bottom is 218nm long and 60nm wide, rotated 60° clockwise. The relative positions of the centers of the three rectangles are represented by coordinates as ①(0nm, 0nm), ②(-50nm, 22nm), and ③(-27 nm, -172nm). The optical switch unit structure is shown in Figure 1. Figure 2 As shown, from bottom to top are SiO2 substrate, 100nm thick Au, 100nm thick ITO, and 50nm thick gold structure.

[0040] The incident light is incident from above at an angle of 30° (the angle with the length direction of the first rectangular structure ① is 30°) on the metal micro-nano structure area. The incident light passes through the upper chiral metasurface structure layer and the ITO layer, and is reflected on the bottom Au film. The reflected light passes through the ITO layer and the chiral metasurface structure layer in turn, and is emitted from the upper surface at an angle of 30°. When the incident light is right-handed circularly polarized light, at 1340nm, the chiral metasurface structure absorbs the incident light more, resulting in a smaller reflectivity, so the emitted light is smaller, and this is the off state in the all-optical switch. When using 45MW / cm 2When the laser pumps the sample, the refractive index of the sample changes due to the third-order nonlinear effect of ITO, and the spectrum red-shifts, so the reflectivity increases at 1340nm. The reflectivity at this time is higher, that is, the output light is higher, and this is the on-off point in the all-optical switch. The on-off ratio of RCP light at a wavelength of 1340nm reaches 5.16.

[0041] CD value is Figure 5 Before pumping, the maximum CD value appeared at 1340nm, with a peak value of 0.636, showing polarization-selective reflection of LCP light and RCP light. After pumping, the CD spectrum was red-shifted, with a peak CD value of 0.666 at 1440nm. Although the spectrum was red-shifted, the CD value remained high, showing a high selectivity for circularly polarized light.

Claims

1. A circular polarization selective ultrafast all-optical switch based on a zero-refractive index material metasurface, characterized in that: A 100-200 nm thick Au film is deposited on a SiO2 substrate by vacuum thermal evaporation, a 100-120 nm thick ITO film is deposited on the Au film by magnetron sputtering coating technology, and a periodically arranged metal Au micro-nano structure layer is prepared on the ITO film; Each metal micro-nanostructure in the periodically arranged metal micro-nanostructure layer: from the perspective of looking down at the metal micro-nanostructure layer, it includes three different rectangular structures: the first rectangular structure ① is 504 nm long and 55 nm wide; the second rectangular structure ② is 261 nm long and 100 nm wide; the third rectangular structure ③ is 218 nm long and 60 nm wide; the first rectangular structure ① strings the second rectangular structure ② and the third rectangular structure ③ together, and the second rectangular structure ② and the third rectangular structure ③ are strung together along the length direction of the first rectangular structure ①, that is, they intersect with the first rectangular structure ① at the same time, the second rectangular structure ② is located in the upper part of the length direction of the first rectangular structure ①, and the length direction of the second rectangular structure ② rotates clockwise relative to the length direction of the first rectangular structure ① to form an angle θ1, θ1 is 50°; the third rectangular structure ③ is located in the lower part of the length direction of the first rectangular structure ①, and the length direction of the third rectangular structure ③ rotates clockwise relative to the length direction of the first rectangular structure ① to form an angle θ2, θ2 is 60°; The relative positions of the centers of the three rectangles are represented by coordinates. The coordinates of the center of the first rectangular structure ① are (0 nm, 0 nm), the coordinates of the center of the second rectangular structure ② are (-50 nm, 22 nm), and the coordinates of the center of the third rectangular structure ③ are (-27 nm, -172 nm).

2. A circular polarization selective ultrafast all-optical switch based on a zero-refractive index material metasurface according to claim 1, characterized in that: The thickness of the metal micro-nano structure layer, that is, the thickness of the three rectangles, is 50 nm.

3. A circular polarization selective ultrafast all-optical switch based on a zero-refractive-index metasurface according to claim 1, characterized in that: The periodic arrangement is arranged in sequence at least along the width direction of the first rectangular structure ①.

4. The circular polarization selective ultrafast all-optical switch based on a zero-refractive index material metasurface according to claim 1, characterized in that: The incident light is incident on the metal micro-nano structure area from above at an angle of 30°. The incident light passes through the upper chiral metasurface structure layer and the ITO layer, and is reflected on the bottom Au film. The reflected light passes through the ITO layer and the chiral metasurface structure layer in turn, and is emitted from the upper surface at an angle of 30°. When the incident light is right-handed circularly polarized light, at 1340nm, the chiral metasurface structure absorbs the incident light more, resulting in a smaller reflectivity, so the emitted light is smaller, which is the off state in the all-optical switch. When 45 MW / cm 2 When the sample is pumped by laser, the refractive index of the sample changes and the spectrum red-shifts due to the third-order nonlinear effect of ITO, so the reflectivity increases at 1340 nm. The reflectivity at this time is higher, that is, the output light is higher, and this is the on state in the all-optical switch.

5. A method for preparing a circular polarization selective ultrafast all-optical switch based on a zero-refractive index material metasurface according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Au film is deposited on SiO2 substrate using vacuum thermal evaporation process; (2) Using magnetron sputtering coating technology, continue to deposit ITO film on the Au film; (3) Using electron beam lithography to process a mask in the shape of a metal micro-nano structure on the ITO film; (4) Au is evaporated using a vacuum thermal evaporation process to prepare a periodically arranged metal micro-nanostructure on the ITO film.